Atividade turística e relações socioambientais: o setor Esplanada no município de Rio Quente (GO) - 1990 a 2014 - (:unkn) unknown (Universidade Federal de Goiás, 2015)
Humanity's constant search to know and understand the nature and its transformations leads us to questions and in-depth studies, especially listing the actions of Homo sapiens itself as a major modifier of the medium. In this context, we propose to investigate the tourism, with its social and environmental issues, limited and restricted to Rio Quente municipality (GO) through a comparison between the years 1990 and 2014. In addition to the permissive factor for economic development, tourism aroused the interest of scientists and geographers due to environmental impacts, forcing public and private managers to take responsibility and different postures. Thus, this work presents reflections considering the important concepts of Geography in the tourism approach and analysis of the environmental impacts of this activity. To this end, different stages were developed: literature searches, field and / or laboratory. Thus, it appears, at first, one of Tourism Geography literature; in a second time a review of the history of tourism; In a third step in a dialogue with the various authors dealing with the social and environmental impacts; and on the fourth time, we present an analysis of the perception of the human population on the Rio Quente municipality in this regard. Considering the peculiarity of the region, the tourist concentration on his unique place in Sector Esplanada and its great distance from the center and other districts of the city, it was decided to define the sector Esplanada as the main focus of the study. Tourism in Rio Quente municipality (GO), as analyzed, showed an exponential growth after the 1990 The increase in the number of tourists caused, hence the increase in public revenue from tourist activities in Sector Esplanada. This growth showed, however, various environmental issues and the transformation of the local landscape, especially in the sector in question who were the pillars of this study. The results obtained allow us to understand how the tourism phenomenon has influenced the new forms of appropriation and use of space, its commercialization, the willingness of the local culture and landscape. Further, the work allowed the identification of positive and negative impacts generated by tourism activity and turn to issues such as jobs, recreation for the local population, quality of life, income, among others. Therefore, the dissertation discuss the issue of tourism in this municipality goiano through the various concepts and the reality experienced by the native local population, serving as a reference, including, for improved management or actions to balance the identified environmental impacts. To extract relevant information when searching and studying the environmental and tourism issues, this dissertation added information regarding the concepts of geography, specifically, the positive and negative impacts that permeate tourism in Rio Quente (GO). This reflection involves, above all, the local human population, enabling the participation of citizens in the construction of the study, which contributed to the consistent thread of scientific reasoning, aligning it with the theoretical framework presented. The research presented here can only be considered an initiative, a tool and even a warning to the public and private agencies in Rio Quente municipality (GO) and surrounding with regard to the perception that local people have the their environmental projects in Sector Esplanada, to show their satisfaction or dissatisfaction, when comparing the application of economic resources in the 1990-2014 period.
Tourist activities and environmental relations: sector Esplanada in county Rio Quente (GO) in the years 1990 - 2014
Keywords: Geografia do turismo; História do turismo; Impactos socioambientais do turismo; Rio Quente (GO); Tourism geography; History of tourism; Social and environmental impacts of tourism; GEOGRAFIA HUMANA::GEOGRAFIA URBANA